The Gaia ultracool dwarf sample - I. Known L and T dwarfs and the first Gaia data release - Smart, Ricky L.; Caballero, José A. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. We identify and investigate known ultracool stars and brown dwarfs that are being observed or indirectly constrained by the Gaia mission. These objec